PEMUNGUTAN PAJAK BERULANG TERHADAP INSTANSI PENGGUNA JASA LAYANAN RESTORAN SEBAGAI PINTU MASUK BAGI KORUPSI HASIL PAJAK - Tita, Heillen Martha Yosephine (Faculty of Law, Universitas Pattimura, 2020)
Recurring tax collection is a tax imposition process where the payment is made by the same party against the same tax object with different capacities and time. This act is more common in Restaurant service user agencies in the accountability of activities contained in theBudget Implementation Documen. In ist implementation, the process becomes an entry poit to corrupt practice of tax revenues, because there are indication of errors in the targets. This legal issue is assessed using the judicial normative type method with a statutory approach and conceptual approach,as well as collaborationg with the study of the concept of collection and collection, the concept of tax and restaurant tax and the concept of autorithy as an analysis tool.